Epigenetics in the formation of pathological aggregates in amyotrophic lateral sclerosis - Noches, Veronica; Campos-Melo, Danae; Droppelmann, Cristian A.; Strong, Michael J. (Frontiers in Molecular Neuroscience, 2024)
The progressive degeneration of motor neurons in amyotrophic lateral sclerosis (ALS) is accompanied by the formation of a broad array of cytoplasmic and nuclear neuronal inclusions (protein aggregates) largely containing RNA-binding proteins such as TAR DNA-binding protein 43 (TDP-43) or fused in sarcoma/translocated in liposarcoma (FUS/TLS). This process is driven by a liquid-to-solid phase separation generally from proteins in membrane-less organelles giving rise to pathological biomolecular condensates. The formation of these protein aggregates suggests a fundamental alteration in the mRNA expression or the levels of the proteins involved. Considering the role of the epigenome in gene expression, alterations in DNA methylation, histone modifications, chromatin remodeling, non-coding RNAs, and RNA modifications become highly relevant to understanding how this pathological process takes effect. In this review, we explore the evidence that links epigenetic mechanisms with the formation of protein aggregates in ALS. We propose that a greater understanding of the role of the epigenome and how this inter-relates with the formation of pathological LLPS in ALS will provide an attractive therapeutic target.